2019
DOI: 10.1016/j.appet.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Association between eating frequency and eating behaviours related to appetite from 4 to 7 years of age: Findings from the population-based birth cohort generation XXI

Abstract: ReuseThis article is distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs (CC BY-NC-ND) licence. This licence only allows you to download this work and share it with others as long as you credit the authors, but you can't change the article in any way or use it commercially. More information and the full terms of the licence here: https://creativecommons.org/licenses/ TakedownIf you consider content in White Rose Research Online to be in breach of UK law, please notify us by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
3
7
0
1
Order By: Relevance
“…The present results revealed that higher consumption of ultraprocessed products at 4 years of age was positively associated with higher scores in food fussiness at 7 years of age, regardless of child and maternal characteristics. This finding confirms previous evidences that children exhibiting less healthy dietary patterns early in life may later have some problematic eating behaviours related to appetite (10,24,36,37) . Fussy eating has been described as a common problem among young children (10,24,(36)(37)(38)(39) , with a peak incidence at approximately 2 years of age, and that tends to decrease as the child grows older and is exposed to a wide variety of foods (22,37,40) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results revealed that higher consumption of ultraprocessed products at 4 years of age was positively associated with higher scores in food fussiness at 7 years of age, regardless of child and maternal characteristics. This finding confirms previous evidences that children exhibiting less healthy dietary patterns early in life may later have some problematic eating behaviours related to appetite (10,24,36,37) . Fussy eating has been described as a common problem among young children (10,24,(36)(37)(38)(39) , with a peak incidence at approximately 2 years of age, and that tends to decrease as the child grows older and is exposed to a wide variety of foods (22,37,40) .…”
Section: Discussionsupporting
confidence: 91%
“…These cohort findings showed that the intake of ultra-processed foods and beverages was somewhat stable from 4 to 7 years of age. Dietary pattern stability throughout childhood corroborates other studies that observed some level of tracking in the same age span (24,34,36) . Even though the Portuguese children's ultraprocessed consumption is relatively low in comparison with other child populations and has shown stability over the period analysed, the slight increase in consumption should be considered alarming because it may limit the consumption of homemade meals from unprocessed, minimally or moderately processed foods.…”
Section: Discussionsupporting
confidence: 89%
“…The meal definitions have been described previously (Vilela et al, 2019). Briefly, an “eating occasion” was any occasion when food or drink was consumed 30 min apart and provided a minimum of 210 kJ (50 Kcal) of energy.…”
Section: Methodsmentioning
confidence: 99%
“…Obesity has a multifactorial character, among its main causes, and environmental factors stand out, such as socioeconomic conditions, lifestyle, and eating habits [2,[5][6][7][8][9]. Several instruments are used to assess food intake, which is one of the aspects of eating behavior [5,8,[10][11][12][13][14][15][16][17][18][19]. However, there is no foolproof assessment of the food consumption method [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional knowledge alone does not guarantee healthy eating habits because the actual behavior is dependent on food beliefs, taboos, and so on [25,27]. Children's eating behavior is most susceptible to external interference because they are not the ones purchasing and preparing the food they consume [11,17,[26][27][28][29], in addition to attitudes, control practices, and beliefs of family members in relation to their food that directly influence the construction of eating habits even in childhood [9,15,25,30,31].…”
Section: Introductionmentioning
confidence: 99%